2020
DOI: 10.1002/art.41403
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti–Topoisomerase I Antibodies of the IgM Isotype With Disease Progression in Anti–Topoisomerase I–Positive Systemic Sclerosis

Abstract: Objective Anti–topoisomerase I (anti–topo I) autoantibodies in systemic sclerosis (SSc) are associated with diffuse skin involvement and interstitial lung fibrosis. Thus far, however, the relationship between anti–topo I antibody response and disease course has not yet been fully evaluated. This study was undertaken to gain insight into the association between characteristics of the anti–topo I antibody response and clinical disease course in SSc patients positive for anti–topo I antibodies. Methods Levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Most of them have nuclear targets and are SSc-specific ( 3 ). Some studies suggested that IgG ATA+ titers correlate with severity, and recent data showed that IgM ATA+ titers are associated with disease activity ( 17 , 18 ). Finally, autoantibodies have been found in the sera of individuals years before SSc onset ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them have nuclear targets and are SSc-specific ( 3 ). Some studies suggested that IgG ATA+ titers correlate with severity, and recent data showed that IgM ATA+ titers are associated with disease activity ( 17 , 18 ). Finally, autoantibodies have been found in the sera of individuals years before SSc onset ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data indicate that ATAs can bind directly to the surface of fibroblasts in SSc patients, but it remains unknown whether this binding could lead to fibroblast activation (49). Another study associated the presence of IgM ATAs with disease progression in ATA (+) SSc patients, but no pathogenetic involvement has been yet established (50) (51). Through a series of experiments, the authors showed that Topo I could bind directly to fibroblasts and recruit ATAs.…”
Section: Pathogenetic Aspects Of B Cells In Sscmentioning
confidence: 99%
“…Other reports pointed out the frequent presence of anti-RNA-Polymerase III antibodies in patients who developed SRC [ 19 , 56 ]. Anti-topoisomerase1 antibodies are instead associated with disease progression and poor outcome of SRC [ 20 , 57 ]. The use of high doses of corticosteroids has been associated with an increased risk of SRC, as demonstrated by several retrospective studies [ 49 , 50 , 58 ].…”
Section: Kidney Involvement In Systemic Sclerosismentioning
confidence: 99%
“…The upregulated B cells lead to the production of a plethora of autoantibodies, such as anti-topoisomerase I and anti-centromere antibodies. While anti-topoisomerase I antibodies are usually associated with diffuse and severe SSc [ 18 , 19 , 20 ], anti-centromere antibodies are associated with the CREST syndrome or lcSSc [ 21 , 22 ]. Among other autoantibodies, those targeting endothelial cells, including endothelin type A receptor and angiotensin II type I receptor, induce activation or apoptosis of endothelial cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%